O ensino da Saúde Pública Veterinária nos cursos de graduação em Medicina Veterinária da região Sudeste do Brasil - Cruz, Carolina de Alvarenga [UNESP] (2015)
A globalized world demands professionals who are able to focus on the concept One world, one health. Therefore, veterinarians play a very important part in health management. Also, formal Veterinary Medicine education should be concerned in instructing professionals who are fit to meet the needs required by the society. Thus, the objective of this research was to accomplish a diagnosis of the situation involving Veterinarian Public Health teaching in Veterinary Medicine undergraduate courses in southeastern Brazil, in addition to defining the profile of undergraduate students in this regions' Veterinary Medicine courses. This research was conducted through analysis of course curricula and, in order to define students' profiles, we have elaborated and applied two types of individual surveys. The results showed that the subjects do not address adequately the area of Veterinary Public Health. Also, in this context, it is clear that the veterinary healing profile is emphasized at the expense of a preventive one, because the courses' subjects related to the area have restricted working hours, and are offered only in the final periods of the course, which discourages the student in finding new possibilities offered by the profession he chose. As regards the student profile, one can see that the undergraduate student body is mostly composed of females, joins the institution at a young age - not being sure of its choice concerning its profession -, usually opts for this career based on its fondness for animals, has a pre-formed clinical view and persists in focusing in a curative and not preventive veterinary medicine. Therefore, it is necessary to restructure veterinary medicine education, so that the egress can meet the global demands and can ...